2017
DOI: 10.1101/gad.292235.116
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation activates a peptidase that promotes cleavage and destabilization of its activating E3 ligases and diverse growth regulatory proteins to limit cell proliferation in Arabidopsis

Abstract: The characteristic shapes and sizes of organs are established by cell proliferation patterns and final cell sizes, but the underlying molecular mechanisms coordinating these are poorly understood. Here we characterize a ubiquitinactivated peptidase called DA1 that limits the duration of cell proliferation during organ growth in Arabidopsis thaliana. The peptidase is activated by two RING E3 ligases, Big Brother (BB) and DA2, which are subsequently cleaved by the activated peptidase and destabilized. In the cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 42 publications
0
114
1
Order By: Relevance
“…Family M102 (DA1 peptidase), omitting contaminants, is restricted to Streptophyta and had its origin presumably in the ancestor to that phylum. The DA1 peptidase is ubiquitin-dependent and degrades a deubiquitinating enzyme, and regulates cell proliferation [60]. Family N11 (intein-containing chloroplast ATPdependent peptide lyase) probably originated in the ancestor of chlorophytes, but homologues, presumably the result of horizontal gene transfers, are also found in some euryarchaeotes, bacteria, fungi and dsDNA viruses.…”
Section: Peptidase Families With An Origin In Plantsmentioning
confidence: 99%
“…Family M102 (DA1 peptidase), omitting contaminants, is restricted to Streptophyta and had its origin presumably in the ancestor to that phylum. The DA1 peptidase is ubiquitin-dependent and degrades a deubiquitinating enzyme, and regulates cell proliferation [60]. Family N11 (intein-containing chloroplast ATPdependent peptide lyase) probably originated in the ancestor of chlorophytes, but homologues, presumably the result of horizontal gene transfers, are also found in some euryarchaeotes, bacteria, fungi and dsDNA viruses.…”
Section: Peptidase Families With An Origin In Plantsmentioning
confidence: 99%
“…Recently, increasing evidence has indicated that the ubiquitin receptor DA1, a conserved component of the ubiquitin-proteasome pathway, has important functions in regulating seed size. In Arabidopsis thaliana, DA1 functions partially redundantly with one of its homologs, DA1-RELATED 1 (DAR1), to control seed size by restricting the period of cell proliferation in maternal integuments (Dong et al, 2017;Li et al, 2008). The dominant-negative mutant da1-1 carries a G-to-A mutation in DA1, causing an R-to-K change in the conserved amino acid at position 358 (DA1 R358K ).…”
Section: Introductionmentioning
confidence: 99%
“…In rapeseed (Brassica napus) and maize (Zea mays), the overexpression of a similar mutant form of DA1 or DAR1 homologs also improved their seed weights and organ sizes, thereby increasing the overall grain yield and biomass (Wang et al, 2017a;Xie et al, 2018). Furthermore, a loss-of-function T-DNA DA1 mutant (da1-ko1) in Arabidopsis also caused an increase in seed size, indicating that DA1 can be studied relatively independently of DAR1 in regulating seed size (Dong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest example of an N-end rule substrate identified using such information is that of the organ-size regulator BIG BROTHER, which is cleaved by the protease DA1 in Arabidopsis. The resulting C-terminal fragment then appears to be targeted for degradation by the N-recognin PRT1 (Dong et al, 2017). It is also worth noting that the recently discovered defensive functions of the Ac/ and Arg/N-end rule pathways are coherent with a potential role of defense-related plant proteases (including MetAPs) in generating N-end rule substrates.…”
Section: Met-pro Promentioning
confidence: 96%